Engineered Allosteric Regulation of Protein Function. Issue 17 (15th September 2022) - Fauser, Jordan; Leschinsky, Nicholas; Szynal, Barbara N.; Karginov, Andrei V.
Graphical abstract: Highlights: Bioengineered allostery provides a method for spatiotemporal regulation of proteins. GPCR chimeras are used to dissect signaling of a structurally homologous protein family. Inserted allosteric switch domains offer broad applicability to protein regulation. Allosterically regulated synthetic proteins provide tools to study cell signaling. Abstract: Allosteric regulation of proteins has been utilized to study various aspects of cell signaling, from unicellular events to organism-wide phenotypes. However, traditional methods of allosteric regulation, such as constitutively active mutants and inhibitors, lack tight spatiotemporal control. This often leads to unintended signaling consequences that interfere with data interpretation. To overcome these obstacles, researchers employed protein engineering approaches that enable tight control of protein function through allosteric mechanisms. These methods provide high specificity as well as spatial and temporal precision in regulation of protein activity in vitro and in vivo . In this review, we focus on the recent advancements in engineered allosteric regulation and discuss the various bioengineered allosteric techniques available now, from chimeric GPCRs to chemogenetic and optogenetic switches. We highlight the benefits and pitfalls of each of these techniques as well as areas in which future improvements can be made. Additionally, we provide a brief discussion on implementation of engineered allosteric regulation approaches, demonstrating that these tools can shed light on elusive biological events and have the potential to be utilized in precision medicine.